Industry 4.0 (Brussels, 2016)
"This study, prepared by Policy Department A at the request of the ITRE committee, analyses the Industry 4.0 Initiative which encompasses the digitalisation of production processes based on devices autonomously communicating with each other along the value chain. It considers the potential of the initiative and business paradigm changes and impacts of this transformation. The study assesses the rationale for public intervention and outlines measures that could be adopted to increase the gains and limit the threats from Industry 4.0."